Insights into the Feelings, Thoughts, and Behaviors of Children with Visual Impairments: A Focus Group Study Prior to Adapting a Cognitive Behavior Therapy–Based Anxiety Intervention. (May 2017) - Visagie, Lisa; Loxton, Helene; Stallard, Paul; Silverman, Wendy K.
Introduction: Anxiety is the most common psychological problem reported among children with visual impairments. Although cognitive behavior therapy interventions have proven successful in treating childhood anxiety, it is unclear whether they are suitable and accessible for children who have visual impairments. This study aimed to determine if and how traditional cognitive behavior therapy–based interventions could be adapted for use with this specific population by interviewing children with visual impairments themselves. Methods: A qualitative research design was used. Sixteen children with visual impairments (aged 9 to 13 years) participated in two focus group interviews. Participants attended two special schools in the Western Cape, South Africa. Interviews were audio-recorded and transcribed verbatim, and content analysis was undertaken. Results: Three primary themes emerged from the focus group data: (1) difficulties encountered by children with visual impairments; (2) existing coping strategies; and (3) insight into the concepts of feelings, thoughts and behaviors (central to cognitive behavior therapy). Discussion: The emergent themes and their implications for the adaptation of a cognitive behavior therapy–based anxiety intervention are discussed. Implications for practitioners: Results provide practitioners with guidelines to consider when using or adapting therapeutic techniques such as cognitive behavior therapy for children with visual impairments.